Pengaruh Penggunaan Aplikasi Tiktok Sebagai Media Dakwah di Kalangan Mahasiswa Muslim UPI - Muhamad Parhan (IAIN Padangsidimpuan, 2022)
The TikTok application is a short video provider platform that is being loved by millennials from all walks of life, including students. Students who are generally aged 18 to 25 years are the younger generation who should have full responsibility for their lives. He must be able to distinguish between what is good and what is bad, what he needs and what he doesn't need, and what is useful for him and what is not. Departing from this, the authors want to know the effect of using the Tiktok platform in terms of Islamic da'wah to Muslim students at UPI. The research approach uses a qualitative approach by using an online questionnaire method with a random sample with the condition that the respondents must be UPI students and are Muslim. The questionnaire was filled out by 50 respondents with the results that the average respondent knew the Tiktok application and used it as entertainment for them and saw the da'wah messages conveyed through Tiktok. The content creator of da'wah who often fyp on Tiktok the respondents are Ustad Hanan Attaki. The use of the Tiktok application is considered quite influential as a medium of propaganda among UPI Muslim students.